Unusual causes of peritonitis in a peritoneal dialysis patient: Alcaligenes faecalis and Pantoea agglomerans - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; TİGEN, ELİF; ARIKAN, İZZET HAKKI; ODABAŞI, ZEKAVER (BMC, 2011)
An 87-year-old female who was undergoing peritoneal dialysis presented with peritonitis caused by Alcaligenes faecalis and Pantoea agglomerans in consecutive years. With the following report we discuss the importance of these unusual microorganisms in peritoneal dialysis patients.